Incidence and outcomes of thoracic aortic injuries with regionalized care in a mature trauma system. (January 2019) - Harris, Donald G; Rabin, Joseph; Crawford, Robert S; Klyushnenkova, Elena N; Drucker, Charles B; Chen, Hegang; Scalea, Thomas M; Diaz, Jose J
Introduction: Thoracic aortic injury is a leading cause of death after blunt trauma, but the effect of trauma system organization on outcomes is undefined. This was an analysis of thoracic aortic injury in a state with a comprehensive trauma system. Methods: This was a retrospective study of thoracic aortic injury in Maryland between 2009 and 2014 using a statewide inpatient admission database. Presence of thoracic aortic injury and open or endovascular aortic interventions were identified by International Classification of Diseases version 9 codes. Patients were compared by admitting hospital status, categorized as Level I or non-Level I trauma centers. Outcomes were overall inpatient mortality and death after aortic repair. Results: Of 774, 211 injured patients, 168 (0.02%) had thoracic aortic injury. Patients with thoracic aortic injury were younger, more often male, and were more severely injured than patients without thoracic aortic injury. The majority of patients (136, 81%) were admitted to Level I trauma centers; Level I and non-Level I patients had similar characteristics. Most patients (110, 65%) were managed non-operatively, but patients admitted to Level I facilities were more likely to undergo aortic repair. Overall and post-operative mortality rates were lower at Level I hospitals (22% versus 31% and 6% versus 17%, respectively), but these differences did not reach statistical significance. Conclusion: This novel analysis indicates thoracic aortic injury management in Maryland is highly concentrated at Level I trauma centers, which was associated with mortality below previously reported national rates. Although limited by small sample size, these findings suggest a benefit to regionalized care for patients with thoracic aortic injury and support transfer to high-volume facilities for definitive management.